Soil metatranscriptome demonstrates a shift in C, N, and S metabolisms of a grassland ecosystem in response to elevated atmospheric CO2 - Rosado-Porto, David; Ratering, Stefan; Moser, Gerald; Deppe, Marianna; Müller, Christoph; Schnell, Sylvia (Frontiers in Microbiology, 2022)
Soil organisms play an important role in the equilibrium and cycling of nutrients. Because elevated CO2 (eCO2) affects plant metabolism, including rhizodeposition, it directly impacts the soil microbiome and microbial processes. Therefore, eCO2 directly influences the cycling of different elements in terrestrial ecosystems. Hence, possible changes in the cycles of carbon (C), nitrogen (N), and sulfur (S) were analyzed, alongside the assessment of changes in the composition and structure of the soil microbiome through a functional metatranscriptomics approach (cDNA from mRNA) from soil samples taken at the Giessen free-air CO2 enrichment (Gi-FACE) experiment. Results showed changes in the expression of C cycle genes under eCO2 with an increase in transcript abundance for carbohydrates and amino acids uptake, and degradation, alongside the increase in transcript abundance for cellulose, chitin, and lignin degradation and prokaryotic carbon fixation. In addition, N cycle changes included a decrease in transcript abundance of the N2O reductase, involved in the last step of the denitrification process, which explains the increase of N2O emissions in the Gi-FACE. Also, a shift in nitrate (NO3-) metabolism occurred, with an increase in transcript abundance for the dissimilatory NO3- reduction to ammonium (NH4+) (DNRA) pathway. S metabolism showed increased transcripts for sulfate (SO42-) assimilation under eCO2 conditions. Furthermore, soil bacteriome, mycobiome, and virome significantly differed between ambient and elevated CO2 conditions. The results exhibited the effects of eCO2 on transcript abundance from C, N, S cycles, and the soil microbiome. This showed the direct connection between eCO2 and the increased greenhouse gas emission as well as the importance of soil nutrient availability to the balance of soil ecosystems.